Development of Kahoot-based Learning Media in Geography Subjects - Khairil, Khairil; Suasti, Yurni; Ernawati, Ernawati (Postgraduate School, Universitas Negeri Padang, 2021)
To create an effective learning atmosphere in the classroom, teachers need to use various types of media. One of the media that can be used in geography learning is learning by using Kahoot. This study aims to determine the feasibility of the Kahoot application as a geography learning medium. The type of research used is Research and Development (R&D). This study uses the ADDIE development research model, with the following development stages Analysis; Design; Development; Implementation; and Evaluation. The results of validation by material experts with an average percentage of 87% with very decent criteria. Media expert validation results with an average percentage of 85% with very decent criteria. The results of the small group trials of students with an average of 84% with very decent criteria. The results of large group trials on students with an average of 84%. So it can be concluded that the development of Kahoot-based geography learning media is feasible to use in geography learning.